IL-18/IL-18R Signaling Is Dispensable for ILC Development But Constrains the Growth of ILCP/ILCs - Xie, Mengying; Zhang, Mingying; Dai, Mengyuan; Yue, Shan; Li, Zhao; Qiu, Ju; Lu, Chenqi; Xu, Wei (Frontiers in Immunology, 2022)
Innate lymphoid cells (ILCs) develop from ILC progenitors in the bone marrow. Various ILC precursors with different ILC subsets lineage potentials have been identified based on the expression of cell surface markers and ILC-associated key transcription factors reporter genes. This study characterized an IL-7Rα+IL-18Rα+ ILC progenitor population in the mouse bone marrow with multi-ILC lineage potential on the clonal level. Single-cell gene expression analysis revealed the heterogeneity of this population and identified several sub-populations with specific ILC subset-biased gene expression profile. The role of IL-18 signaling in the regulation of IL-18Rα+ ILC progenitors and ILC development was further investigated using Il18- and Il18r1-deficient mice, in vitro differentiation assay and adopt transfer model. IL-18/IL-18R mediated signal was found to not be required for early stages of ILC development. While Il18r1-/- lymphoid progenitors were able to generate all ILC subsets in vitro and in vivo like the wild-type counterpart, increased IL-18 level, as often occurred during infection or under stress, suppressed the growth of ILCP/ILC in an IL-18Ra-dependent manner via inhibiting proliferation and inducing apoptosis.